Non competitive general equilibrium with endogenous price setting (2001)
This article presents an equilibrium concept that, contrary to the traditional walrasian one, allows for the unbalance between supply and demand in different markets, making easier the analysis of those situations in which they differ persistently, as in the case of the labor market. Furthermore, the process of price setting becomes endogenous and it is shown that an equilibrium with endogenous price setting is a particular case of an equilibrium of fixed prices. Toward the end some examples are presented which help us to sustain these arguments.